A Severe Case of Hantavirus Cardiopulmonary Syndrome in a Patient Presenting as STEMI - Dobrica Diana; Udroiu Cristian Alexandru; Galrinho Ruxandra Drăgoi; Borjog Tudor; Vinereanu Dragos (Journal of Cardiovascular Emergencies, 2023)
Hantavirus cardiopulmonary syndrome (HCPS) is a rare disease caused by Hantaviruses, that are transmitted from rodents to humans through aerosols. In some patients, HCPS can have a severe evolution, with rapid progression to respiratory distress and cardiogenic shock. We present the case of a 56-year-old female patient who was transferred to our hospital with ST-segment elevation myocardial infarction (STEMI) and acute respiratory distress syndrome (ARDS). The coronary angiography showed normal epicardial coronary arteries and the lung computed tomography (CT) raised the suspicion of tracheoesophageal fistula, which was soon refuted by an upper digestive endoscopy. Initially, the evolution was very severe, requiring mechanical ventilation, hemodynamic support, and broad-spectrum antibiotics. Later, sero-logical testing revealed an acute infection with Hantavirus Dobrava type. The patient lives in a rural environment, working in a wheat mill. Despite the severe presentation, the evolution was favorable, with complete remission of the pulmonary and myocardial damage after 2 weeks. We emphasize the importance of HCPS suspicion and specific testing in the early phase of the disease, as well as early admission to an intensive care unit, which is crucial in severe cases and can improve survival in a patient without any specific symptoms or a clear diagnosis.